2015
DOI: 10.1038/srep08057
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of circular RNA abundance with proliferation – exemplified with colorectal and ovarian cancer, idiopathic lung fibrosis and normal human tissues

Abstract: Circular RNAs are a recently (re-)discovered abundant RNA species with presumed function as miRNA sponges, thus part of the competing endogenous RNA network. We analysed the expression of circular and linear RNAs and proliferation in matched normal colon mucosa and tumour tissues. We predicted >1,800 circular RNAs and proved the existence of five randomly chosen examples using RT-qPCR. Interestingly, the ratio of circular to linear RNA isoforms was always lower in tumour compared to normal colon samples and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
565
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(606 citation statements)
references
References 31 publications
39
565
0
2
Order By: Relevance
“…Cancer Bachmayr-Heyda and colleagues were the first to report a global reduction of circRNA abundance in colorectal cancer cell lines and cancer tissues compared to normal tissues, and they discovered a negative correlation between global circular RNA abundance and proliferation. 42 Further study by RNAseq analyses of normal and cancerous tissues identified a large number of circRNA candidates. 16 Among these candidates, many were differently expressed between normal and cancerous tissues, suggesting a potential role of circRNA in cancer.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Cancer Bachmayr-Heyda and colleagues were the first to report a global reduction of circRNA abundance in colorectal cancer cell lines and cancer tissues compared to normal tissues, and they discovered a negative correlation between global circular RNA abundance and proliferation. 42 Further study by RNAseq analyses of normal and cancerous tissues identified a large number of circRNA candidates. 16 Among these candidates, many were differently expressed between normal and cancerous tissues, suggesting a potential role of circRNA in cancer.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…And the abnormality of gene expression and biological behavior observed in cancer cells may be considered the result of deregulated circRNA function. 11,38 Interestingly, the versatility of circRNA expression mainly lies in post-transcriptional regulation, which is frequently achieved by RNA-RNA interactions. 24 CircRNAs, together with some other ceRNAs, are believed to serve as microRNA reservoirs, but with much more binding sites, which enable the circRNAs to specialize in harboring microRNAs.…”
Section: Biogenesis and Functionmentioning
confidence: 99%
“…A circular RNA encoded as Hsa_circ_002059 has already been determined to be significantly downregulated in gastric cancer. 37,38 In addition, several circRNAs are considered responsible for the malignant biological behavior of cancer cells. Thus, in this review, we mainly discuss the roles of circRNAs in cancer tissues by engaging in regulation of microRNA.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…The expression of circular RNAs has recently been reported to generally decrease in human cancers 53 and increase as flies age, 47 suggesting that their expression can be drastically altered and potentially contribute to pathological states. However, the biological functions of most circular RNAs are still completely unclear.…”
Section: 304142mentioning
confidence: 99%